ANODE MICROARC OXIDATION OF ALUMINIUM PISTONS — PECULIARITIES OF THE TECHNOLOGY OF THE HEAT-RESISTING COVER APPLYING - V. V. Ovchinnikov; V. Ja. Zelinskij (Литьë и металлургия, 2004)
In the article there are given the technological peculiarities of putting of the thermal covering on combustor of the diesel engine aluminium forcer by method of micro-arc oxidations.